Molecular identification and characterization of Humicola insolens isolates - PATHAK, ASHUTOSH (Mushroom Research, 2018)
In present investigation twelve morphologically distinct isolates of H.insolens which were isolated from Agaricus bisporus compost samples of different geographical regime, different type of composting methods and substrates of compost were characterized and differentiated on the basis of DNA analysis in order to validate the correct identity and diversity on genus and species level by Internal Transcribed Spacer. RAPD, multiple sequence alignment and bootstrapping. .ITS confirm all twelve isolates were H.insolens as clear band was observed Â between 500-600bp. After confirmation of isolates on genus level the intraspecies diffrentiation were confirmed by multiple sequence alignment, RAPD and bootstrap analysis. On the basis of analysis the isolates were grouped in to seven clades and one of the isolates from geographically distinct region Meghalaya formed an out-group. In groups sub groups are also formed. Isolates in seven clades or groups although shows morphological variation to each other but genetically most of the isolates were similar to each other and form four distinct group irrespective of seven morphological groups which were totally different isolates to each other in morphological as well as on molecular level.Â